Comprehensive analysis of cuproptosis-related long non-coding RNA signature and personalized therapeutic strategy of breast cancer patients - Guo, Qiaonan; Qiu, Pengjun; Pan, Kelun; Lin, Jianqing (Frontiers in Oncology, 2022)
Background: Breast cancer (BC) is considered to be one of the primary causes of cancer deaths in female. Cupropotosis was suggested to play an important role in tumor proliferation and tumor immune microenvironment. Therefore, an investigation was conducted to identify the relationship between cuproptosis-related lncRNAs and BC prognosis. Method: Based on The Cancer Genome Atlas (TCGA), 9 cuproptosis-related lncRNAs were identified by Pearson analysis and Cox regression analysis to create a cuproptosis-related lncRNA signature. Subsequently, Patients with BC were divided into high-risk and low-risk groups. The Kaplan-Meier curves and a time-dependent ROC analysis were employed to elucidate the predictive capability of the signature. After that, the KEGG pathway analysis was conducted by Gene Set Enrichment Analysis (GSEA) and the lncRNA-mRNA co-expression network was established by Cytoscape software. Furthermore, the ESTIMATE score was calculated and the immune cell type component analysis was conducted. Eventually, immunotherapy response analysis was applied to identify the predictive power of cuproptosis-related lncRNAs to tumor immunotherapy response, including immune checkpoint genes expression levels, tumor mutation burden (TMB) and microsatellite instable (MSI). Results: Patients with BC in low-risk groups shown better clinical outcomes. The KEGG pathways in high-risk groups were mainly enriched in immune response and immune cell activation. Furthermore, the ESTIMATE scores were higher in low-risk groups and the immune cell infiltrations were dramatically different from high-risk groups. The low-risk groups were shown higher infiltration level of CD8+ T cell and TMB-high status, resulting in better response to immunotherapies. Conclusion: The findings of this study revealed that the 9-cuproptosis-related lncRNA risk score was an independent prognostic factor for BC. This signature was a potential predictor for BC immunotherapy response. What we found will provide novel insight for immunotherapeutic treatment strategies in BC.